2017
DOI: 10.1590/1414-431x20176306
|View full text |Cite
|
Sign up to set email alerts
|

Association between Toll-like receptor 4 Asp299Gly polymorphism and coronary heart disease susceptibility

Abstract: Published data on the association between Toll-like receptor 4 (TLR4) Asp299Gly polymorphism and coronary heart disease (CHD) susceptibility are inconclusive. To derive a more precise estimation of the relationship, a meta-analysis was performed. English-language studies were identified by searching PubMed and Embase databases (up to November 2016). All epidemiological studies were regarding Caucasians because no TLR4 Asp/Gly and Gly/Gly genotypes have been detected in Asians. A total of 20 case-control studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
(17 reference statements)
1
1
0
Order By: Relevance
“…By contrast, Morange et al demonstrated that this SNP is not a significant predictor of the CV risk in healthy individuals [46]. These data are in line with the results of two meta-analyses based on 12 and 20 case-control studies, in which nonassociation of this SNP with CV diseases was proven [23,47]. And also, in the present study, no correlation between this genetic variant and the occurrence of preexisting CV diseases could be shown.…”
Section: Snps and The Cardiovascular Prognosis In The 3-yearsupporting
confidence: 91%
“…By contrast, Morange et al demonstrated that this SNP is not a significant predictor of the CV risk in healthy individuals [46]. These data are in line with the results of two meta-analyses based on 12 and 20 case-control studies, in which nonassociation of this SNP with CV diseases was proven [23,47]. And also, in the present study, no correlation between this genetic variant and the occurrence of preexisting CV diseases could be shown.…”
Section: Snps and The Cardiovascular Prognosis In The 3-yearsupporting
confidence: 91%
“…The results for rs4986790 were in line with those of 2 prior meta-analyses. 35,36 However, we could not exclude the possibility that rs4986790 along with other factors may have a synergistic effect on CAD risk. Boekholdt et al found that among patients with coronary atherosclerosis, cardiovascular events, including myocardial infarction, were significantly decreased when statins were administered to carriers of the rs4986790 G allele.…”
Section: Discussionmentioning
confidence: 99%